MANAJEMEN PENINGKATAN MUTU SARANA DAN PRASARANA PENDIDIKAN DI MADRASAH TSANAWIYAH WAHID HASYIM BADEGAN PONOROGO - Nadia Lailatul Fitriani; Harjali (Pascasarjana IAIN Ponorogo, 2021)
According to Permendiknas No. 13 of 2007 concerning the competencies of principals, it was stated that a principal/madrasah must have five competencies namely personality competence, managerial competence, entrepreneurial competence, supervision competency and social competence. A madrasah head as a manager is required to be able to have managerial readiness in managing eight national education standards, one of which is the standard of educational infrastructure. Based on the survey, the condition of educational infrastructure in Madrasah Tsanawiyah Wahid Hasyim Badegan Ponorogo has decreased even in the last ten years which has decreased the number of students and student achievement. But since the 2017/2018 school year with the existence of a new madrasah head, the quality of infrastructure has improved. The madrasah head develops more managerial competencies in improving the quality of infrastructure in his madrasah. So that it succeeded in increasing student achievement such as the champion of the drumb band competition in Ponorogo Regency, had a computer laboratory that could be used for the Computer Based National Examination (UNBK) for 9th grade students, had a two storey building for teacher's room, madrasah head room, and classrooms. His study aims to explain the managerial competence of madrasa principals in improving the quality of educational infrastructure in Madrasah Tsanawiyah Wahid Hasyim Badegan Ponorogo in terms of management functions which include planning, organizing, implementing and controlling. Data collected through interviews, observations, and documentation. The validity of the data is measured by lengthening observations, perseverance of observations, triangulation, discussions with peers and checking. Data analysis through data collection, data reduction, data presentation and drawing conclusions. The results showed the headmaster of madrasa did four things for the management of improving the quality of educational infrastructure. First, planning to carry out the program (1) madrasa head with the foundation and the committee set the goal of improving the quality and quantity of madrasas by improving the quality of educational infrastructure (2) meetings involving foundations, committees, teachers, employees to determine the priority scale of Sarpras in the form of procurement of complete drumband equipment, the addition of music band instruments, the addition of habsyi equipment, the creation of computer laboratories and the construction of buildings for the teacher's room, madrasah headroom, and classrooms, (3) recruiting new teachers who are willing to not work in other institutions. Second, organizing (1) division of labor according to ability based on the meeting of leaders with all deputy head of madrasa, (2) grouping work into three divisions: procurement of computers, building construction, computer laboratories, (3) determination of relations between parts of the organization, through hierarchy authority restrictions. Division members to the division coordinator, then to wakasarpras then to the headmaster of the madrasa, (4) coordination of all divisions. Through regular meetings every Saturday, communication is immediately interrupted by teaching, and communication with mobile phones. Third, implementation by (1) moving all personnel to carry out the task according to the target, using motivational techniques in the form of reward and punishment, (2) calling the problematic teacher or employee to the madrasah headroom to be directed, (3) providing a modest incentive to the task implementer. Fourth, control by conducting (1) setting building standards based on Ministry of Education Regulation No. 33 of 2008, set a two-semester Sarpras realization tarjet, (2) performance appraisal through matching reality with the standards according to standards such as achievements and achievements, two-story building being built, computer laboratories materialized so that UNBK class IX can be used, (3) making corrections and find a way out by increasing fundraising for building improvements.